Lightweight geopolymer-based hybrid materials. (1st November 2017) - Roviello, Giuseppina; Menna, Costantino; Tarallo, Oreste; Ricciotti, Laura; Messina, Francesco; Ferone, Claudio; Asprone, Domenico; Cioffi, Raffaele
Abstract: The present study reports on the preparation and characterization of new organic-inorganic geopolymer based hybrid foams obtained by reacting an aluminosilicate source and an alkalisilicate solution with mixtures of dialkylsiloxane oligomers or organic resins precursors. By using different amounts of Si 0 powder as in situ foaming agent, hybrid geopolymer-based foams with densities ranging from 0.25 to 0.85 g/cm 3 were successfully prepared. These new materials are characterized by remarkable mechanical properties, good fire resistance and low thermal conductivity, significantly better than those shown by neat geopolymer foams reported in the literature and comparable or even better than those of typical (not geopolymer) inorganic foamed materials with similar densities. Graphical abstract: Highlights: Hybrid geopolymer-based foams with densities ranging from 0.25 to 0.85 g/cm 3 were obtained. By using Si 0 powder as in situ foaming agent, a homogeneous and very regular foaming process was obtained. Improved properties in respect to neat geopolymer foams and inorganic foamed-materials with similar densities.